2009
DOI: 10.1007/s11548-009-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

The virtual reality tool VirSSPA in planning DIEP microsurgical breast reconstruction

Abstract: VirSSPA provides additional and potentially more accurate data over conventional CTA with regard to the site of the best perforators and its course through the muscle for DIEP micro-vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It could help the teaching of junior trainees in the art of assessing patients and to do virtual reality navigation and dissection before surgery [20]. However, until we improve tactile platforms for virtual dissection, this is not reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…It could help the teaching of junior trainees in the art of assessing patients and to do virtual reality navigation and dissection before surgery [20]. However, until we improve tactile platforms for virtual dissection, this is not reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Forty patients proposed for uni (35) or bilateral [5] breast reconstruction, either immediate or delayed, were included after signing the informed consent to participate in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Software tools to enhance identification and characterization of perforators have been proposed in the past. VirSSPA, for example, is a virtual reality tool allowing the imaging team to show results of their self-analysis to the surgical team in a 3D environment [5]. In another study, a plugin was developed to make the delineation of perforators and their characterization easier [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additional information that can be obtained by CTA includes venous communication between the right and left abdomen, cutaneous perforators, as well as other parameters that can be used to calculate flap viability and flap weights, all of which can help preoperative planning by surgical teams [3,25,26]. Recent research has shown that 3-D postprocessing of CTA data may also improve accuracy in identifying perforators [6,[27][28][29]. CTA has been accepted as the gold standard in preoperative planning for DIEP flaps with sensitivity of 96% for all perforators and sensitivity of 100% for perforators > 1 mm [30].…”
Section: Preoperative Imagingmentioning
confidence: 99%